We have to talk about it: Bringing fertility into the conversation for young women with breast cancer. Issue 16 (22nd April 2021) - Taylor, Caitlin E.; Meisel, Jane Lowe
Abstract : At the time of a diagnosis with breast cancer, many women under the age of 45 years may not have completed family planning. Fertility‐related concerns can affect treatment decision‐making and adherence, and this study by Sella et al highlights the need to incorporate fertility into the conversation early and over time so that patients′ quality of life and cancer outcomes can be optimized.